PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS KEHUTANAN PROVINSI SULAWESI SELATAN - Andi Rahmawati; Andi Abdul Razak Ishak; Sarifah Sarifah (Bajang Institute, 2022)
The purpose of this study was to determine the influence of leardership and communication on employee performance at Dinas Kehutanan Provinsi Sulawesi Selatan. the types of data used in this study are qualitative and quantitative data sources are primary data and secondry data calculation are carried out using the SPSS application with the multiple linear regeneration method, the correlation coefficient of determination and the t test with a sample size 31 employees. The results of this study indicate that. Multiple linear regeneratioan Y 13, 695 Y + 2,614 X1 + 2,401 x2 Â the correlation coefficient is r 3,340 and the test with the result of X1 test tcount > ttable (2, 614 + 1,701) and the results of test tcount > ttable (2,401 + 1.701). So that it can be seen that there is an influence positive and significant between leadership and communication on employee performance at the south Dinas Kehutanan Sulawesi Sealatan